The environment and its impact on the language of Ali bin al-Jahm Semantic analysis Description of the camel as a model (Journal of the College of Basic Education, 2022)
Since the instinct and the ancient traditions that imprinted the Arab taste with its character and which settled in the unconscious in the soul of the writer, this study came to address the frameworks that show the impact of the environment on the language of the poet, which had a prominent role in building the Arabic poem, especially with regard to the words of the poem, and what it carries Meanings and similes, and this environment is the nature represented by the geographical location and what it includes of a nomadic or urban character.There is no doubt that the environment has a great impact on building the personality of the creative writer, with what surrounds him, so every person affects and is affected by his environment according to the elements and tools that this environment contains. different from other environment